Sebuah Jurnal ANALISIS KINERJA LALULINTAS AKIBAT ADANYA KEGIATAN PUSAT PERBELANJAAN (Studi Kasus Jalan Ahmad Yani, Jalan Ketintang dan Persimpangan Jalan Ahmad Yani-Jalan Ketintang Surabaya) - Rahan Ardiansyah, Mohamad; Teki Tjendani, Hanie (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
The growth of commercial areas in urban areas, especially shopping centers, has contributed significantly to the increase in traffic volume. This study aims to analyze the influence of Royal Plaza visitor activities on traffic volume and degree of saturation on the Jalan Ahmad Yani network, Jalan Ketintang, and the Ahmad Yani-Ketintang intersection in Surabaya City. The method used refers to the Indonesian Road Capacity Guidelines (PKJI) 2023, with primary data collection through a traffic volume survey for four days in three time periods (day, evening, night), then analyzed to obtain capacity values, actual volume, and degree of saturation (DS) on each road segment. The results of the analysis show that the highest traffic volume was recorded at 5444.70 SMP/hour on Jalan Ahmad Yani, with a road capacity of 5115.64 SMP/hour, resulting in a degree of saturation (DS) value of 1.06. This value indicates that the level of road service is in category F, which reflects very saturated traffic conditions and congestion. Meanwhile, the Ahmad Yani–Ketintang intersection shows DS ranging from 0.85 to 1.19, depending on peak times. This finding confirms that the presence of Royal Plaza places a significant traffic burden on the surrounding road network, and a traffic management strategy is needed to mitigate the impact and improve road service performance.